Answer:
c
Step-by-step explanation:
Answer:
Point form : (1,1)
Equation form : x=1 , y=1
Step-by-step explanation: Solve for the first variable in one of the equations, then substitute the result into the other equation.
Hope this helps you out! ☺
Answer:
Midpoint of (-1,-5) and (-5,7) is (-3,1)
Midpoint of (5,-2) and (-4,2) is (0.5,0)
Step-by-step explanation:
Use the midpoint formula
C and D.............................
(2/5)+(3/(5x))=(x+5)/10
nasty fractions, we hates it forever
so
get rid of all those nasty fractions
multiply both sides by 10x
4x+6=x(x+5)
distribute
4x+6=x^2+5x
minus (4x+6) from both sides
0=x^2+x-6
factor
0=(x-2)(x+3)
set each to zero
0=x-2
2=x
0=x+3
-3=x
x=-3 and 2
3rd option is answer